2021
DOI: 10.2147/amep.s309440
|View full text |Cite
|
Sign up to set email alerts
|

Medical Students’ Attitude and Perception Towards Basic Medical Science Subjects at Wollo University, Northeast Ethiopia

Abstract: Introduction The knowledge of basic medical science could help to remember a fact and be used to understand causal mechanisms of disease process that improve the accuracy of diagnostic formulations. Objective To assess the perception and attitude of medical students towards basic medical science subjects along with retention rate and clinical relevance in Wollo University. Methods Institutional-based cross-sectional study design was employed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 30 publications
(36 reference statements)
1
4
0
Order By: Relevance
“…This finding was in agreement with studies conducted in Ethiopia, Malaysia and South Asia, which revealed that there are few opportunities in basic medical science, which are limited to teaching, research, and diagnostic laboratories. 15,20,21 The current study also showed that nearly two third of medical students perceived that integrated curriculum with other basic sciences increased their interest in ward embryology course. This finding was higher than a reported study by Teshome et al which revealed only one third of medical students perceived that integrated curriculum with other basic sciences increased their interest in ward histology course.…”
Section: Dovepresssupporting
confidence: 56%
“…This finding was in agreement with studies conducted in Ethiopia, Malaysia and South Asia, which revealed that there are few opportunities in basic medical science, which are limited to teaching, research, and diagnostic laboratories. 15,20,21 The current study also showed that nearly two third of medical students perceived that integrated curriculum with other basic sciences increased their interest in ward embryology course. This finding was higher than a reported study by Teshome et al which revealed only one third of medical students perceived that integrated curriculum with other basic sciences increased their interest in ward histology course.…”
Section: Dovepresssupporting
confidence: 56%
“…This finding is in agreement with Teshome et al reports. 28 Regarding different methods of teaching histology, our study reveals that there were 82.61% of participants who agreed or strongly agreed with the proposed integration of histology and pathology. Furthermore, a system approach to teaching pathology in conjunction with other disciplines was preferred by 70.1%, which was consistent with previous researches.…”
Section: Discussionmentioning
confidence: 75%
“…This finding is in line with the study conducted in Ethiopia, China, Malaysia, and South Asia, which found that there is a limited opportunity in basic medical science, restricted to teaching, research, and diagnostic laboratories. 28 , 29 In our study, nearly one-third of the medical students acknowledge the significance of the integration of histology with clinical discipline, which helps in a better understanding of respective subjects. However, 34.24% of those polled said the integrated curriculum had not increased their interest in basic medical sciences.…”
Section: Discussionmentioning
confidence: 80%
“…A survey among medical undergraduates has shown that only 47% of students consider biochemistry as clinically relevant, while only 26% of them were able to recall biochemistry during clinical discussions. 6 It is absolutely necessary to change this attitude of medical students by making the subject interesting. Hence case based learning and problem based learning avenues were undertaken.…”
Section: Discussionmentioning
confidence: 99%
“…Classroom teaching was supplemented with weekly written assignments that enhanced daily learning and has helped them to perform better in the formative assessments as supposed by students. A survey among medical undergraduates has shown that only 47% of students consider biochemistry as clinically relevant, while only 26% of them were able to recall biochemistry during clinical discussions 6 . It is absolutely necessary to change this attitude of medical students by making the subject interesting.…”
Section: Discussionmentioning
confidence: 99%